2017
DOI: 10.1007/s11892-017-0951-7
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Fasting and Caloric Restriction

Abstract: Calorie restriction triggers a complex series of intricate events, including activation of cellular stress response elements, improved autophagy, modification of apoptosis, and alteration in hormonal balance. Intermittent fasting is not only more acceptable to patients, but it also prevents some of the adverse effects of chronic calorie restriction, especially malnutrition. There are many somatic and potentially psychologic benefits of fasting or intermittent calorie restriction. However, some behavioral modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
2
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(132 citation statements)
references
References 109 publications
1
116
2
13
Order By: Relevance
“…Finally, differences between this study and previous reports could be due to implementing time-restricted feeding and prevention of overeating, which improves peripheral metabolism (Anton et al, 2018;Golbidi et al, 2017;Manoogian and Panda, 2017), potentially altering neurometabolism in aged rats regardless of diet. The majority of studies utilizing aged rodents have provided access to food ad libitum throughout the lifespan, resulting in metabolically impaired subjects (Martin et al, 2010).…”
Section: Discussioncontrasting
confidence: 62%
“…Finally, differences between this study and previous reports could be due to implementing time-restricted feeding and prevention of overeating, which improves peripheral metabolism (Anton et al, 2018;Golbidi et al, 2017;Manoogian and Panda, 2017), potentially altering neurometabolism in aged rats regardless of diet. The majority of studies utilizing aged rodents have provided access to food ad libitum throughout the lifespan, resulting in metabolically impaired subjects (Martin et al, 2010).…”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies showed that long‐term strict energy limitation (5 weeks, 50% intake of the control group) may cause brain 5‐HT system dysfunction, leading to the development of depression and anxiety 100 . Otherwise, strict energy limitation might lead to malnutrition 101 and other metabolic dysfunctions in the body. Our group found that 9‐hour acute CR increased BDNF level in the PFC and hippocampus, resulting in neurogenesis in the subgranular region and producing anti‐depressant‐like effects 27 .…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…CR has been performed for the study of physiological and metabolic mechanisms as well as the intracellular signaling pathways leading to weight reduction and improved glucose homeostasis (Golbidi et al, 2017;Veyrat-Durebex et al, 2009). One of the most stable outcomes in animal models of CR is a restitution in glucose tolerance (Matyi et al 2018) and correction of weight by loss of adipose tissue (Dommerholt et al 2018).…”
Section: Impact Of Cr To Enhance Coordinated [Ca 2+ ]I and Gap Junctmentioning
confidence: 99%